2013
DOI: 10.1353/hpn.2013.0056
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Teacher Education Programs and Community Engagement

Abstract: Theories of situated knowledge support that knowledge involves experience of practices rather than just accumulated information. While an important segment of foreign language teacher education programs focuses on the theoretical component of second/foreign language acquisition theories and relevant methodological concerns, it is mainly through practice that novice teachers construct their new professional identities. Consequently, typical teacher preparation programs require a number of classroom practice hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Important tangible benefits noted by many studies were access to the university and its resources, such as student-volunteers (Oberg De La Garza & Moreno Kuri, 2014;Schaffer, Hargate, & Marong, 2015;Valaitis et al, 2016). Similarly, many case studies reported that their CSL/CUP increased the assets of community members or the organization, such as participant health benefits, skill development, organizational capacity, and social integration (Apatu, Slawson, & Gonzalez, 2013;Bucher, 2012;Costandius et al, 2014;Jovanović & Filipović, 2013;Wilson, 2016). Tangible costs associated with CSL/ CUP outcomes include draining community and organizational resources for student training and supervision (Blouin & Perry, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Important tangible benefits noted by many studies were access to the university and its resources, such as student-volunteers (Oberg De La Garza & Moreno Kuri, 2014;Schaffer, Hargate, & Marong, 2015;Valaitis et al, 2016). Similarly, many case studies reported that their CSL/CUP increased the assets of community members or the organization, such as participant health benefits, skill development, organizational capacity, and social integration (Apatu, Slawson, & Gonzalez, 2013;Bucher, 2012;Costandius et al, 2014;Jovanović & Filipović, 2013;Wilson, 2016). Tangible costs associated with CSL/ CUP outcomes include draining community and organizational resources for student training and supervision (Blouin & Perry, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Prema istraživanjima u našoj zemlji, profesori jezika i dalje primenjuju tradicionalne metode u praksi, iako sve više pribegavaju novim pristupima, usklađujući svoju uobičajenu praksu sa novim nastavnim tendencijama (Pejović/ Jovanović, 2012;Đukić Mirzayantz, 2017;Pejović/Andrijević, 2017). U tom smislu, u učionici se koriste metodi zasnovani na komunikativnim zadacima i metodi aktivno orijentisane nastave (Jovanović/Filipović, 2013).…”
Section: Ikt U Nastavi Jezika Pre Pandemije Covid-19unclassified
“…For example, in the 2013 Hispania special issue The Scholarship of Community Engagement: Advancing Partnerships in Spanish and Portuguese (not reporting any study on Portuguese, however), Barreneche and Ramos‐Flores (), Carney (), Ebacher (), Hartfield‐Méndez (), and other authors published in the journal beyond that special issue (e.g., Pellettieri, ) departed from the guest editors’ premise, shared with intercultural citizenship theory, that “it is an advantage as well as a challenge trying to teach the utilitarian aspects of languages while also connecting them to other more humanistic goals” (Hellebrandt & Jorge, 2013, p. 209). While Hartfield‐Méndez () addressed internationalization needs explicitly, Bugel (); Lear and Sánchez (); Tijunelis, Satterfield, and Benkí (2013); and Petrov (), among others, fell within the “within one country” option together with Tacelosky () and Jovanović and Filipović ()—the only two cases outside the United States (Mexico and Serbia, respectively). J. García, Pierce, and Zambrano () described a study abroad option in which American college students collaborated with Ecuadorian adolescents to produce short films.…”
Section: Literature Reviewmentioning
confidence: 99%